INVENTARISASI DAN KATALOGISASI KOLEKSI PUSTAKA/BUKU BACAAN PERPUSTAKAAN KELURAHAN SERANGAN, KECAMATAN DENPASAR SELATAN, KOTA DENPASAR - Erviantono, Tedi (Buletin Udayana Mengabdi, 2012)
The village library faces some difficulties in terms of the lack of documentation of the reading materials which have not yet been well identified. The Community Service was done in Serangan Library Denpasar Sekatan- Denpasar to give knowledge about everything to do with library. The activity aimed at giving easier method how to utilize library, therefore it included how to identify, classify and documentary the reading materials in that library. This activity also tried to inventory and catalog 814 books using Dewey system. It was done in two steps, namely workshop and inventory, catalog of reference collection.